Block Copolymer Self-assembled and Cross-linked Nanoassemblies for Combination Delivery of Iron Oxide and Doxorubicin - Daniel Scott, Yihwa Beabout , Robert J. Wydra, Mo Dan, Robert Yokel, J. Zach Hilt and Younsoo Bae (Journal of Applied Pharmaceutical Science, 2013)
We describe the development of nanoscale polymer drug carriers for the combinational delivery of an anticancer drug (doxorubicin: DOX) along with super paramagnetic iron oxide nanoparticles (IONPs). The drug molecules were electrostatically loaded into both block copolymer self-assembled nanoassemblies (SNAs) and cross-linked nanoassemblies (CNAs). Both nanoassemblies entrapped DOX and IONPs either individually or in tandem, maintaining sub-100 nm diameter. The IONP-loaded nanoassemblies generated heat in the presence of an alternating magnetic field (AMF). Incorporation of the drug payload, DOX, showed no adverse effects on the heating profile. Drug release from the SNAs and CNAs was accelerated as temperature increased from the normal body temperature (37°C) to a mild hyperthermic condition (40 ï¾ 42°C). CNAs released DOX faster than SNAs regardless of an incubation temperature. CNAs co-entrapped IONPs and DOX were more stable than SNAs in aqueous solutions for five days. These results suggest that block copolymer cross-linked nanoassemblies provide viable delivery platforms for combination delivery of inorganic molecules, anticancer drugs, and potentially other various biologically active substances.
Keywords: Nanoassemblies, nanoparticle, block copolymers, drug